Neutralizing antibody response to Omicron subvariants BA.1 and BA.5 in children and adolescents following the two-dose CoronaVac protocol (Immunita-002, Brazil): a 12-month longitudinal study - Corsini, Camila Amormino; Campos, Guilherme Rodrigues Fernandes; Martins, Priscila Fernanda da Silva; Filgueiras, Priscilla Soares; Lima, Ana Esther de Souza; Gomes, Sarah Vieira Contin; Curimbaba, Caroline De Almeida Leitao; Lorencini, Daniela Aparecida; Morandi Junior, Eolo; da Silva, Victor Mattos; Cervi, Maria Célia; Borges, Marcos de Carvalho; et al. (Frontiers in Immunology, 2025)
IntroductionThe covid-19 pandemic prompted an unprecedented global effort to develop and deploy vaccines, including CoronaVac, an inactivated virus-based vaccine. While these vaccines effectively reduced severe cases and hospitalizations, limited data exists on their immunogenicity in younger populations, particularly children and adolescents. Understanding the immune response in these groups is essential to guide vaccination strategies and assess protection against emerging variants of concern, such as Omicron subvariants BA.1 and BA.5. This study evaluated the neutralizing antibody response in children and adolescents aged 3–17 years over 12 months following the two-dose CoronaVac protocol in Brazil.MethodsA cohort of 108 children (3–11 years) and adolescents (12–17 years) from Serrana, Brazil, received two doses of CoronaVac. Peripheral blood samples were collected at baseline, and at 1, 3, 6, and 12 months after the second dose. Participants were stratified by serostatus prior to vaccination. Neutralizing antibodies against Omicron BA.1 and BA.5 were assessed using microneutralization assays.ResultsNeutralizing antibody titers increased significantly after vaccination in both seronegative and seropositive individuals. For seronegative participants, seroconversion rates for BA.5 rose from 16.6% pre-vaccination to 93.3% one month after the second dose in children, and from 50% to 92% in adolescents, with sustained levels for 12 months. Seropositive participants also showed enhanced antibody titers, particularly against BA.5. No significant differences in neutralization between BA.1 and BA.5 were observed post-vaccination, contrary to prior literature, suggesting uniform effectiveness against these subvariants.DiscussionThis study demonstrates that CoronaVac significantly enhances and sustains neutralizing antibody titers in children and adolescents for up to one year, including against immune-evading subvariants like BA.5. The robust response highlights the vaccine’s potential as a critical tool for reducing SARS-CoV-2 transmission and preventing severe disease, particularly in regions with limited access to updated vaccines. Further studies with larger cohorts are needed to validate these findings and inform vaccination strategies for immunoresistant variants.